2019
DOI: 10.1097/brs.0000000000002947
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Preoperative MRI Findings and Surgical Revision Within Three Years After Surgery for Lumbar Disc Herniation

Abstract: Study Design This cohort study was an analysis of prospectively collected data in the DaneSpine Database. Objective: The objective was to determine whether pre-operative magnetic resonance imaging (MRI) findings were associated with the frequency of surgical revision due to recurrent lumbar disc herniation (LDH) within three years after first-time, single-level, simple lumbar discectomy. Summary of Background Data: Because of a risk of poorer outcome in patients receiving revision surgery compared to first-tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
0
8
2
Order By: Relevance
“…SROM, Modic change, and degree of disc degeneration has been confirmed by previous studies to be associated with recurrent LDH after lumbar discectomy. [22][23][24][25][26] In this study, we did not find any significant differences between the 2 groups in the surgical segment Modic change and degree of disc degeneration. However, we found that the SROM of the RLN group was significantly higher than that of the Non RLN group (10.3 ± 3.5 vs 8.2 ± 2.9, P < .001).…”
Section: Sromcontrasting
confidence: 52%
“…SROM, Modic change, and degree of disc degeneration has been confirmed by previous studies to be associated with recurrent LDH after lumbar discectomy. [22][23][24][25][26] In this study, we did not find any significant differences between the 2 groups in the surgical segment Modic change and degree of disc degeneration. However, we found that the SROM of the RLN group was significantly higher than that of the Non RLN group (10.3 ± 3.5 vs 8.2 ± 2.9, P < .001).…”
Section: Sromcontrasting
confidence: 52%
“…This is particularly true for patients with L 4/5 herniation; it is difficult to distinguish nerve root compression on MRI because the initial site of the L5 nerve root is thinner and there is less fat space around the nerve roots after separation from the spinal cord [30]. Besides, MRI is difficult to determine scar compression and postoperative arachnoid adhesion, while MRM has high resolution and can be reconstructed in three dimensions, which can assist clinicians to observe nerve roots from many angles [31] and help to guide postoperative rehabilitation. Some previous studies have also shown that MRM has a certain clinical application value in some orthopedic surgeries.…”
mentioning
confidence: 99%
“…Most studies have not found an association between sex and rLDH. 21,24,[26][27][28]30,35 However, Oh et al 20 found that female sex is a risk factor for rLDH, while some studies found men to be more likely to experience recurrence than women. [21][22][23] Li et al 23 and Ziegler et al 24 found that younger age is a risk factor for rLDH.…”
Section: Sex and Agementioning
confidence: 99%